Satisfaction with Professional Training of Graduates of Educational Institutions of the Ministry of Internal Affairs of Russia - Ulyanina O.A (Moscow State University of Psychology and Education, 2019)
Rationale and relevance: the collection and analysis of objective information about the success service graduates institutional schools at the initial stage of professionalization allows you to define promising directions in system of professional training of employees of law-enforcement field and to adjust the educational process in accordance with the needs of operational activities. Objective: to study the satisfaction with the quality of educational services by their consumers (graduates) and employers (managers). The research method is a questionnaire survey of managers and graduates, including four sections. The first section assessed the readiness of graduates to carry out professional activities. The second section assessed the General cultural, business and personal qualities of graduates. The third and fourth sections identified shortcomings and advantages in the training of specialists. the article describes the results of a survey of managers and graduates regarding satisfaction with the quality of educational training. Description of research procedure and sampling: the survey was conducted a year after graduation from educational organizations, it took part 319 of the heads of the expert, investigative and operational units of the Moi of Russia in Volgograd region and 348 graduates of the Volgograd Academy of the MIA of Russia. Among 204 interviewees and evaluate the graduate of the specialty "Legal national security", 53 "Judicial expertise" and 91 "law Enforcement" 2008-2012 set. Results of the study: a high level of professional training was revealed in 59% of graduates of police operatives, 61% - investigators, 60% - experts. The average level of training by mentors was observed in 39% who graduated from the Academy with a degree in "Forensic examination", "Legal support of national security" and 40% - "law Enforcement". The results of the comparative analysis of the expert evaluation of managers and self-assessment showed that graduates are able to adequately assess the level of formation of the necessary competencies. This conclusion is confirmed by the results of the correlation analysis (the lowest correlation coefficient was 0.55). In conclusion, taking into account the results indicated the need for a systematic analysis of the effectiveness of educational and psychological training, the effectiveness of professional activities of graduates of educational institutions of the Ministry of internal Affairs of Russia.